2023
DOI: 10.1021/acs.molpharmaceut.2c00898
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Delivery of Vancomycin from Collagen-tethered Peptide Vehicles for the Treatment of Wound Infections

Abstract: Despite the great promise of antibiotic therapy in wound infections, antibiotic resistance stemming from frequent dosing diminishes drug efficacy and contributes to recurrent infection. To identify improvements in antibiotic therapies, new antibiotic delivery systems that maximize pharmacological activity and minimize side effects are needed. In this study, we developed elastin-like peptide and collagen-like peptide nanovesicles (ECnVs) tethered to collagencontaining matrices to control vancomycin delivery and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 82 publications
4
18
0
Order By: Relevance
“…This formulation process does not employ covalent crosslinking between collagen and HA, which enables a similar collagen fibrillar structure in all samples (as assessed via microscopy analysis of the samples under reflected light at a wavelength of 405 nm, and by microscopic analysis of the autofluorescence of the collagen fibers) . We expect that the range of storage moduli of the samples would be below 100 Pa based on measurements of the storage moduli of collagen (54 Pa) and collagen and fibrin (61 Pa) hydrogels in our prior studies . After gelation at 37 °C for 45 min, the samples were incubated in complete DMEM at 37 °C with 5% CO 2 for 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This formulation process does not employ covalent crosslinking between collagen and HA, which enables a similar collagen fibrillar structure in all samples (as assessed via microscopy analysis of the samples under reflected light at a wavelength of 405 nm, and by microscopic analysis of the autofluorescence of the collagen fibers) . We expect that the range of storage moduli of the samples would be below 100 Pa based on measurements of the storage moduli of collagen (54 Pa) and collagen and fibrin (61 Pa) hydrogels in our prior studies . After gelation at 37 °C for 45 min, the samples were incubated in complete DMEM at 37 °C with 5% CO 2 for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…25 We expect that the range of storage moduli of the samples would be below 100 Pa based on measurements of the storage moduli of collagen (54 Pa) and collagen and fibrin (61 Pa) hydrogels in our prior studies. 27 After gelation at 37 °C for 45 min, the samples were incubated in complete DMEM at 37 °C with 5% CO 2 for 7 days. The culture medium was collected and replaced with fresh culture medium every 2 days.…”
Section: Net Growth Of Ecs Treated Withmentioning
confidence: 99%
“…Bioactive peptides can bind noncovalently to produce a diversity of supramolecular assemblages including nanoparticles and nanofibers, thus enhancing in vivo stability and bioavailability. Based on these characters, a large number of supramolecular assemblages have been extensively designed to form hydrogel and integrate with nanoarchitectures for extending bioapplication. For instance, a self-assembled chelating peptide hydrogel (PPH) was engineered to load with an osteogenic metal ion cluster extracted from the processed pyritum decoction . Since this PPH could regulate a variety of genes related to extracellular matrix synthesis, cell adhesion and migration, and cytokine expression in the process of bone regeneration, PPH would accelerate the progress of various bone healing stages and shorten the bone healing cycle.…”
Section: Classification Of Hydrogelmentioning
confidence: 99%
“…Various CMPs have been investigated as drug delivery carriers, thermosensitive gelators, collagen modification tools, and supramolecular assemblies due to their unique thermoresponsive triple helix formation and collagen binding properties via hydrogen bonding. For example, a thermoresponsive gelator, a CMP-modified 8-arm PEG multiarm polymer, has been reported in a study using CMP as a cross-linking site . Previously, we also reported that multiarm poly­(ethylene glycol) (PEG) (4-arm-PEG-(POG) 10 ) end-modified with (POG) 10 induces gelation by binding between triple helices when mixed with fibrous collagen and has potential for tissue engineering applications .…”
Section: Introductionmentioning
confidence: 99%